Porous Polymersomes with Encapsulated Gd-labeled Dendrimers as Highly Efficient MRI Contrast Agents** - Cheng, Zhiliang (2009)
The use of nanovesicles with encapsulated Gd as MR contrast agents has largely been ignored due to the detrimental effects of the slow water exchange rate through the vesicle bilayer on the relaxivity of encapsulated Gd. Here, we describe the facile synthesis of a composite MR contrast platform, consisting of dendrimer conjugates encapsulated in porous polymersomes. These nanoparticles exhibit improved permeability to water flux and a large capacity to store chelated Gd within the aqueous lumen, resulting in enhanced longitudinal relaxivity. The porous polymersomes, ~130 nm in diameter, were produced through the aqueous assembly of the polymers, polyethylene oxide-b-polybutadiene (PBdEO), and polyethylene oxide-b-polycaprolactone (PEOCL). Subsequent hydrolysis of the caprolactone (CL) block resulted in a highly permeable outer membrane. To prevent the leakage of small Gd-chelate through the pores, Gd was conjugated to PAMAM dendrimer via diethylenetriaminepentaacetic acid dianhydride (DTPA dianhydride) prior to encapsulation. As a result of the slower rotational correlation time of Gd-labeled dendrimers, the porous outer membrane of the nanovesicle, and the high Gd payload, these functional nanoparticles were found to exhibit a relaxivity (R1) of 292,109 mM(−1) s(−1) per particle. The polymersomes were also found to exhibit unique pharmacokinetics with a circulation half-life of >3.5 hrs and predominantly renal clearance.